Storm Surges and Unusual Sea Levels on Israel’s Mediterranean Coast - Striem, H. L. (The International Hydrographic Review, 2015)
Storm surges occurring at Ashdod were investigated. It was found that the daily mean rise of the sea level due to storms may be considered as linearly related to the daily mean of wave heights or to wind velocities near the shore. The rise is about 6 cm per metre of increase in wave height, and about 7 cm for each 10 km/h increase in wind velocity. Most large storms raise the sea level by about 40-50 cm above the previously prevailing level, but in a few instances a short-term upsurge was found superimposed on the gradual daily rise of the storm surge. This additional rise of level is tentatively ascribed to a local storm effect, and might raise the sea level by a further 30-40 cm. Unusually high and low sea levels were also investigated. The basic mean sea level is considered as affected by the daily inequality of the tides, the range of the spring tides, the seasonal and the annual fluctuations o f the sea level, apart from storm effects. Evaluating these contributions it was found that if each factor would act at its maximum the hourly sea level might rise or drop by 1/4 m above or below the extremes (+ 100 cm, — 51 cm relative to the datum level) encountered in the 6 year period investigated.